Integration of Ethnomathematics of Masjid Al Mahdi in Discovery Learning-based Textbook on Students’ Reasoning Ability - Ardiansyah, Adi Satrio; Adi, Yudhi Wahyu; Choirunnisa, Fakhrur Rini; Wardani, Deva Fitria; Raharani, Fatkhiya An-Nisa (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Presenting meaningfulness in the process of learning mathematics is something that must be prioritized to achieve the goals of learning mathematics. One alternative that can be done is through Ethnomatematics integration and the implementation of the Discover Learning model. This research aims to develop. Developing Discovery Learning-based textbook with Ethnomathematics nuances at the Masjid Al Mahdi Magelang on students' reasoning abilities is the aim of this research. Research and development with a modified 4D model into 3D consisting of Define, Design, and Develop has been carried out well. The feasibility validation form, readability form, and student questionnaire form were analyzed descriptively quantitatively to collect the data. From the results, it was obtained the results of the feasibility validation of the textbook with a percentage of 89.40%, the results of the assessment of the readability of textbook with a percentage of 89%, and the results of students' responses to textbook with a percentage of 86.66%. Overall, the textbook with ethnomathematics nuances at the Masjid Al Mahdi Magelang are feasible and easy to understand. It is ready to be implemented in learning mathematics in 8th grade.